Benthos in the nearshore waters off Visakhapatnam - Vijayakumaran, K (Indian Journal of Fisheries, 2011)
The faunal composition, population density, biomass, volume of benthos in relation to sediment, depth range and lat.-long squares off Visakhapatnam were studied. The population density varied from 112 m-2 to 6656 m-2 with an average of 1712 m-2 (1311.88). Biomass ranged between 0.72g m-2 and 42.84g m-2 with an average of 13.43g m-2 ( 9.85). Volume, on the other hand, ranged from 2.81 ml m-2 to 54.77 ml m-2 with an average of 19.76 ml m-2 (13.55). Polychaeta (63 %) was the dominant group of fauna followed by Amphipoda (17 %). Various indices of spatial pattern, richness, diversity, association etc. have been worked out.